Search for a CP-odd Higgs boson decaying into a heavy CP-even Higgs boson and a Z boson in the ℓ + ℓ − t t ¯ $$ {\ell}^{+}{\ell}^{-}t\overline{t} $$ and ν ν ¯ b b ¯ $$ ν \overline{ν}b\overline{b} $$ final states using 140 fb −1 of data collected with the ATLAS detector - The ATLAS collaboration; G. Aad; B. Abbott; K. Abeling; N. J. Abicht; S. H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; B. S. Acharya; C. Adam Bourdarios; et al. (Journal of High Energy Physics, 2024)
Abstract A search for a heavy CP-odd Higgs boson, A, decaying into a Z boson and a heavy CP-even Higgs boson, H, is presented. It uses the full LHC Run 2 dataset of pp collisions at s $$ \sqrt{s} $$ = 13 TeV collected with the ATLAS detector, corresponding to an integrated luminosity of 140 fb −1. The search for A → ZH is performed in the ℓ + ℓ − t t ¯ $$ {\ell}^{+}{\ell}^{-}t\overline{t} $$ and ν ν ¯ b b ¯ $$ ν \overline{ν}b\overline{b} $$ final states and surpasses the reach of previous searches in different final states in the region with m H > 350 GeV and m A > 800 GeV. No significant deviation from the Standard Model expectation is found. Upper limits are placed on the production cross-section times the decay branching ratios. Limits with less model dependence are also presented as functions of the reconstructed m( t t ¯ $$ t\overline{t} $$ ) and m( b b ¯ $$ b\overline{b} $$ ) distributions in the ℓ + ℓ − t t ¯ $$ {\ell}^{+}{\ell}^{-}t\overline{t} $$ and ν ν ¯ b b ¯ $$ ν \overline{ν}b\overline{b} $$ channels, respectively. In addition, the results are interpreted in the context of two-Higgs-doublet models.